Two-year outcomes for the double-blind, randomized, sham-controlled study of targeted lung denervation in patients with moderate to severe COPD: AIRFLOW-2 - Valipour, Arschang; Shah, Pallav; Herth, Felix; Pison, Christophe; Schumann, Christian; Hübner, Ralf-Harto; Bonta, Peter I.; Kessler, Romain; Gesierich, Wolfgang; Darwiche, Kaid; Lamprecht, Bernd; Perez, Thierry; et al. (The International journal of chronic obstructive pulmonary disease, 2020)
Purpose: COPD exacerbations are associated with worsening clinical outcomes and increased healthcare costs, despite use of optimal medical therapy. A novel bronchoscopic therapy, targeted lung denervation (TLD), which disrupts parasympathetic pulmonary innervation of the lung, has been developed to reduce clinical consequences of cholinergic hyperactivity and its impact on COPD exacerbations. The AIRFLOW-2 study assessed the durability of safety and efficacy of TLD additive to optimal drug therapy compared to sham bronchoscopy and optimal drug therapy alone in subjects with moderate-to-severe, symptomatic COPD two years post randomization. Patients and Methods: TLD was performed in COPD patients (FEV1 30-60% predicted, CAT >= 10 or mMRC >= 2) in a 1:1 randomized, sham-controlled, double-blinded multicenter study (AIRFLOW-2) using a novel lung denervation system (Nuvaira, Inc., USA). Subjects remained blinded until their 12.5-month follow-up visit when control subjects were offered the opportunity to undergo TLD. A time-to-first-event analysis on moderate and severe and severe exacerbations of COPD was performed. Results: Eighty-two subjects (FEV1 41.6 +/- 7.4% predicted, 50.0% male, age 63.7 +/- 6.8 yrs, 24% with prior year respiratory hospitalization) were randomized. Time-to-first severe COPD exacerbation was significantly lengthened in the TLD arm (p=0.04, HR=0.38) at 2 years post-TLD therapy and trended towards similar attenuation for moderate and severe COPD exacerbations (p=0.18, HR=0.71). No significant changes in lung function or SGRQ-C were found 2 years post randomization between groups. Conclusion: In a randomized trial, TLD demonstrated a durable effect of significantly lower risk of severe AECOPD over 2 years. Further, lung function and quality of life remained stable following TLD.
Gesehen am 25.01.2021